Matrix metalloproteinase-12 by M2 macrophages induced epithelial to mesenchymal transition in chronic rhinosinusitis with nasal polyps. - Joo-Hoo Park; Jae-Min Shin; Hyun-Woo Yang; Tae Hoon Kim; Seung Hoon Lee; Ok Sarah Shin; Il-Ho Park (PLoS ONE)
Th2 inflammation and epithelial-mesenchymal transition (EMT) play crucial roles in the pathophysiology of chronic rhinosinusitis with nasal polyps (CRSwNP). This study aimed to investigate the hypothesis that MMP-12, produced by M2 macrophages, induces EMT in nasal epithelial cells, thereby contributing to airway inflammation and remodeling in CRSwNP. The expression levels of MMP-12 were measured by RT-PCR in CRS nasal mucosa and THP-1 cells. mRNA and protein levels of E-cadherin, vimentin, α-SMA, and fibronectin were determined using RT-PCR, western blotting, and immunofluorescence staining in primary nasal epithelial cells and air-liquid interface culture. The expression of MMP-12 was significantly increased in CRSwNP and M2-like THP-1 cells. In co-culture with primary nasal epithelial cells and M2-like THP-1 cells, E-cadherin expression was inhibited, and fibronectin, vimentin, and α-SMA expression were increased. MMP-12 decreased E-cadherin but induced fibronectin, vimentin, and α-SMA mRNA and protein expression in primary nasal epithelial cells and air-liquid interface culture. MMP408, an MMP-12 inhibitor, inhibited EMT-related factors. These findings suggest that MMP-12 expression in M2 macrophages induces EMT in nasal epithelial cells and may contribute to the pathogenesis of CRSwNP.